Intracellular linkers are involved in Mg(2+)-dependent modulation of the Eag potassium channel - Liu, Xinqiu (Landes Bioscience, 2010)
Modulation of activation kinetics by divalent ions is one of the characteristic features of Eag channels. Here, we report that Mg(2+)-dependent deceleration of Eag channel activation is significantly attenuated by a G297E mutation, which exhibits a gain-of-function phenotype in Drosophila by suppressing the effect of shaker mutation on behavior and neuronal excitability. The G297 residue is located in the intracellular linker of transmembrane segments S2 and S3, and is thus not involved in direct binding of Mg(2+) ions. Moreover, mutation of the only positively charged residue in the other intracellular linker between S4 and S5 also results in a dramatic reduction of Mg(2+)-dependent modulation of Eag activation kinetics. Collectively, the two mutations in eag eliminate or even paradoxically reverse the effect of Mg(2+) on channel activation and inactivation kinetics. Together, these results suggest an important role of the intracellular linker regions in gating processes of Eag channels.